Short- vs Long-Term Intergenerational Correlations of Employment and Self-Employment in Europe - J. Ignacio Gimenez-Nadal; José Alberto Molina; Jorge Velilla (Institute of Labor Economics (IZA), 2020)
This paper analyzes the existence of short- and long-term intergenerational correlation of employment and self-employment in European countries, using data from the European Union Statistics on Income and Living Conditions. Using longitudinal data for the period 2003-2016, fixed effect estimates show a significant short-term correlation between the current employment status of parents and that of their children. However, short-term correlation of self-employment seems to be driven only by father-son correlations. Conversely, using the special module on Intergenerational Transmissions for the year 2011, estimates show a strong and significant correlation between respondents' self-employment status, and that of their parents when respondents were 14 years old. This suggests that self-employment decisions are not related to short-term family labor supply decisions, but to long-term intergenerational transmission.
Keywords: D65; J62; E24; 330; short- and long-term; Intergenerational transmissions; employment; self-employment; EU-SILC data